Physician Perceptions on Colonoscopy Quality: Results of a National Survey of Gastroenterologists - Ziad F. Gellad; Corrine I. Voils; Li Lin; Dawn Provenzale (Gastroenterology Research and Practice)
Background. Quality indicators for colonoscopy have been developed, but the uptake of these metrics into practice is uncertain. Our aims were to assess physician perceptions regarding colonoscopy quality measurement and to quantify the perceived impact of quality measurement on clinical practice. Methods. We conducted in-person interviews with 15 gastroenterologists about their perceptions regarding colonoscopy quality. Results from these interviews informed the development of a 34-question web-based survey that was emailed to 1,500 randomlyselected members of the American College of Gastroenterology. Results. 160 invitations were undeliverable, and 167 out of 1340 invited physicians (12.5%) participated in the survey. Respondents and nonrespondents did not differ in age, sex, practice setting, or years since training. 38.8% of respondents receive feedback on their colonoscopy quality. The majority of respondents agreed with the use of completion rate (90%) and adenoma detection rate (83%) as quality indicators but there was less enthusiasm for withdrawal time (61%). 24% of respondents reported usually or always removing diminutive polyps solely to increase their adenoma detection rate, and 20% reported prolonging their procedure time to meet withdrawal time standards. Conclusions. A minority of respondents receives feedback on the quality of their colonoscopy. Interventions to increase continuous quality improvement in colonoscopy screening are needed.